Towards an objective measurement of presence, place illusion, and plausibility illusion in virtual reality using electroencephalography - Bahavan, Thiru Thillai Nadarasar; Navaratnarajah, Suman; Owinda, Dulindu; Akalanka, Inoj; Peiris, Roshan; Silva, Anjula De (Virtual reality : the journal of the Virtual Reality Society, 2023)
Presence is a mental state when a user in virtual reality (VR) reacts to events in it as if it is real. Place illusion (PI) and plausibility illusion (PSI) are components of Presence and depend on the Immersion and Coherence of a VR system and the experience. Measuring Presence (PI and PSI) is critical when designing new systems and experiences. However, the traditional questionnaire-based methods of measuring Presence have limitations. Therefore, we propose a method for augmented measurement of Presence, PI, and PSI of VR users with biosignals. For this, we designed a within-subjects experiment that presented VR scenarios with varying levels of Immersion and Coherence while measuring electroencephalography (EEG) of users concurrently. For validation, we took feedback from post-scenario questionnaires presented within the VR environment. The study was conducted with 20 participants. Analyzing the Questionnaire responses revealed that an increase in plausibility illusion or place illusion led to an increase in Presence, confirming the fundamental theory. Analyzing the EEG results revealed that the Envelope Amplitude Correlation features and Spectral Coherence are able to discriminate between the Presence, PI, and PSI of the user. In contrast, there are many entropy features that increase for high PSI.